ICT Integration in 21st-Century Indonesian English Language Teaching: Myths and Realities - Arif Husein Lubis (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract: Albeit profoundly addressed and promoted, limited research-based articles were identified, in particular regarding the Indonesian EFL teachers’ views on ICT integration pertaining to whether it is considered as the real solution to ELT praxis reflecting on their experiences. Thus, the present study was aimed at seeking 13 English teachers’ perception on and attitude toward the implementation of ICT integration. Descriptive qualitative design was used in which a questionnaire consisting of 12 close- and open-ended questions was employed. The data gained were analyzed and displayed descriptively. The findings indicated that even though such framework triggers positive perception, the benefits of the integration were still focused more on the technical levels, not the communicative and functional ones in students’ learning process. Second, time allocation and technical problems became the major constraints to realize such integration. With respect to English education, this study provides a grounding portrait for associated parties to revisit the formulation of ICT integration toward students’ communicative skills. Keywords: ICT integration, English language teaching, perception, attitudesINTEGRASI TIK DALAM PENGAJARAN BAHASA INGGRIS DI INDONESIA ABAD KE-21: MITOS DAN REALITAAbstrak: Meskipun dikaji dan digalakkan, artikel berbasis penelitian terbatas khususnya berkaitan dengan pandangan guru bahasa Inggris di Indonesia tentang apakah integrasi TIK betul-betul menjadi solusi dalam praksis pengajaran bahasa Inggris yang terefleksikan dalam pengalaman mereka. Oleh karena itu, penelitian ini bertujuan untuk mengetahui persepsi dan sikap dari 13 guru bahasa Inggris terhadap integrasi TIK dalam pembelajaran. Penelitian ini menggunakan pendekatan kualitatif dengan teknik deskriptif menggunakan kuesioner sebagai instrumen yang terdiri atas delapan pertanyaan terbuka pilihan ganda dan empat pertanyaan terbuka. Data yang diperoleh dianalisis dengan teknik deskriptif kualitatif. Temuan menunjukkan bahwa walaupun integrasi TIK berdampak pada persepsi positif terhadap keberadaan TIK tersebut, subjek memandang bahwa manfaat integrasi tersebut masih terfokus pada tingkat teknis, bukan pada aspek komunikatif dan fungsional dalam proses belajar siswa. Kedua, alokasi waktu dan masalah teknis menjadi kendala utama untuk mengimplementasikan integrasi tersebut. Studi ini memberikan potret landasan untuk mengkaji kembali perumusan integrasi TIK untuk keterampilan komunikatif siswa, khususnya dalam pendidikan bahasa Inggris. Kata Kunci: integrasi ICT, pengajaran bahasa Inggris, persepsi, sikap